Integrasi Soal Nonrutin dalam Perkuliahan Pemecahan Masalah Matematika: Studi Reflektif Pengajaran - Ulil Nurul Imanah; Fran Susanto (Lembaga Yasin AlSys, 2026)
The low level of university students’ mathematical problem-solving ability remains a challenge in learning, particularly due to the dominance of routine problems, which limits strategic flexibility and hinders the development of metacognitive awareness in dealing with complex problems. This study aims to analyze the impact of integrating non-routine problems, particularly mathematics olympiad problems, into the Mathematical Problem Solving course through a reflective teaching study design. This study used a qualitative approach involving four students in the mathematics education study program over one semester. Data were collected through student worksheets, classroom observations, reflective journals, as well as assessments using a rubric based on heuristic stages encompassing understanding the problem, planning a strategy, carrying out the solution, and reflecting. Data analysis was conducted using an interactive model strengthened by descriptive quantitative indicators. The results showed improvement at all stages of the problem-solving process. The students demonstrated better ability in identifying problem structures, selecting and adjusting strategies, evaluating the effectiveness of solutions, and reflecting on their thinking processes. In addition, there were improvements in strategic flexibility, metacognitive regulation, intellectual perseverance, and the quality of mathematical argumentation. This study concludes that the systematic integration of non-routine problems is effective in developing reflective problem-solving ability. The implications of this study emphasize the importance of using non-routine problems as a pedagogical strategy in mathematics teacher education to develop critical, adaptive, and reflective thinking skills.